2011
DOI: 10.5099/aj110300219
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Leflunomide Analog, UTL-5b (GBL-5b), Suppresses JAK3, MAP3K2, and LITAF Genes

Abstract: UTL-5b (GBL-5b) is a novel analog of leflunomide with anti-inflammatory and antiarthritic effects. It has been shown to lower serum tumor necrosis factor-alpha (TNF-α) level induced by lipopolysaccharide (LPS) in an animal model. In this study, the effect of UTL-5b on nitric oxide (NO) and dihydroorotate dehydrogenase (DHODH) was investigated. Our in vitro studies showed that (1) UTL-5b is a stronger inhibitor of NO production as compared to leflunomide and its active metabolite, teriflunomide, and (2) Unlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…For example, leflunomide has a demonstrated hepatotoxicity [19, 20], while UTL-5g protects liver from cisplatin/radiation-induced damage [21, 22]; leflunomide inhibits dehydroorotate dehydrogenase (DHODH) and is potentially teratogenic, while UTL-5b does not inhibit DHODH [23]. …”
Section: Resultsmentioning
confidence: 99%
“…For example, leflunomide has a demonstrated hepatotoxicity [19, 20], while UTL-5g protects liver from cisplatin/radiation-induced damage [21, 22]; leflunomide inhibits dehydroorotate dehydrogenase (DHODH) and is potentially teratogenic, while UTL-5b does not inhibit DHODH [23]. …”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with what we observed previously in the protective effect of UTL-5g against the toxicity of cisplatin in that elevated TNF- levels were also lowered by UTL-5g [6]. Furthermore, our previous studies showed that a closely related TNF- inhibitor, UTL-5b, significantly suppresses three genes that are relevant to the TNF- pathway: Janus kinase 3 (JAK3), mitogen-activated protein kinase kinase kinase 2 (MAP3K2) and LPS-induced TNF- factor (LITAF) [13,14]. Based on the almost identical structural similarity between UTL-5g and UTL-5b, we believe that the mechanism of UTL-5g may be similar although the theory remains to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…For example, UTL-5b is metabolized by rat microsomes to become 5-methylisoxazole-3carboxylic acid (Isox) and 2-chloroaniline [8]; UTL-5g is quickly converted to Isox and 2,4dichloroaniline (DCA) in the presence of esterase [7]. In terms of pharmacological effects, UTL-5 compounds are similar to leflunomide in that they are both anti-inflammatory and anti-arthritic [11][12][13][14]. However, UTL-5 compounds possess some protective effects which are significantly different from those of leflunomide.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, MICA moiety‐based small molecules have been found to exhibit different biological activities and used as medicines (Figure ) . E.g., Leflunomide and leflunomide analogs ( 3 a ) are immunosuppressive disease‐modifying antirheumatic drug (DMARD) molecules . The MICA derivatives 3 b and 3 c have been evaluated as irreversible human rhinovirus 3C protease inhibitors and DFG‐out p38α inhibitor, respectively .…”
Section: Introductionmentioning
confidence: 99%